Journal of Biomimetics, Biomaterials and Biomedical Engineering. (Journal of Biomimetics, Biomaterials and Biomedical Engineering Ser., 2021)
The 49th volume of "Journal of Biomimetics, Biomaterials and Biomedical Engineering" contains papers that reflect the latest results of scientific research and engineering decisions in the fields of human biomechanics; medical images processing for the goal of various cancer diagnostic; processing and application of electrospun biomaterials and porous bioceramics in the medical practice; new materials and technologies for tissue engineering and drug delivery. We hope that this volume will be useful for many researchers and engineers from the different branches of biomedicine. Biomechanics, Knee Joint, Meniscectome, Fibrocystic Breast, Biomechanical Model, Medical Image Processing, Segmentation, Cancer Diagnosis, Electrospun Biomaterials, Calcium Phosphate, Bioceramics, Drug Delivery, Adipose Stem Cells, Tissue Engineering, Scaffold Materials Science, Bioscience and Medicine, Mechanics.